Process for the synthesis of large size alpha-trihydroaluminum
Patent Information
- Application Number
- CN202410970629.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-19
AI Technical Summary
Existing technologies for preparing large-sized α-aluminum trihydride suffer from complex reaction processes, significant safety risks, small and unstable product sizes, and a lack of effective means to monitor reaction progress.
Large-sized α-aluminum trihydride was synthesized in one step using polysiloxane as a crystallizer. The reaction temperature was reduced, and inert gas protection and vacuum filling technology were used, combined with refractive index monitoring methods to control the deetherification and crystallization process.
This method enables the efficient and safe preparation of high-purity, large-size α-aluminum trihydride, reducing safety hazards, improving product stability and yield, simplifying the process, and ensuring the controllability of the reaction progress.
Smart Images

Figure CN118992975B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen storage materials technology, specifically to a method for synthesizing large-size α-aluminum trihydride. Background Technology
[0002] Aluminum trihydride (AlH3) is an excellent hydrogen storage material with a volumetric hydrogen storage density of 0.148 kg / L, twice that of liquid hydrogen; its gravimetric hydrogen storage density is 10.08 wt%, ranking second among solid light metal hydrogen-containing materials. As a binary hydride, its combustion products are only Al2O3 and H2O, without producing any toxic or harmful substances, making it a clean new energy material. Aluminum trihydride is widely used in aerospace and military fields, often as an additive in solid or solid-liquid hybrid rocket propellants, effectively improving the specific impulse of the fuel.
[0003] AlH3 exists in seven different crystal structures, among which the α-type is the most stable and, to date, the only practically useful crystal form. In its synthesis, the α-type aluminum trihydride can be directionally prepared by controlling the reaction conditions. The hydrogen release temperature of aluminum trihydride is related not only to the crystal form but also significantly to the crystal size; larger crystals result in higher hydrogen release temperatures. In aerospace and military applications, aluminum trihydride needs to be mixed with other fuels, requiring high hydrogen release temperatures. Therefore, a high-quality, large-size aluminum trihydride synthesis method is necessary.
[0004] Patent CN106957046A discloses an improved process for preparing α-aluminum trihydride. It involves preparing an ether compound at low temperature, filtering the clear ether compound solution using a filtration device, and then adding it to a hot toluene solution for deetherification. Patent CN109970030A discloses a synthesis process for α-aluminum trihydride. It involves filtering out a clear filtrate, heating the filtrate to prepare a slurry, and then adding the lower solid layer to heated toluene for deetherification. Patent CN107098313A discloses a method for preparing α-aluminum trihydride. It involves filtering out a clear filtrate, adding it to a heated toluene solution twice for deetherification, and heating the reaction system after each addition of the filtrate.
[0005] The aforementioned patents all employ a conventional "wet" synthesis process, requiring two steps. The primary raw materials are LiAlH4 and AlCl3, which are used to synthesize the associative compound in diethyl ether or a diethyl ether / aromatic hydrocarbon solution. Then, α-AlH3 is obtained by deetherification and crystallization via thermal cracking in an inert aromatic hydrocarbon solution or under vacuum conditions. A representative chemical reaction process is as follows.
[0006] AlCl3 + nEt2O → AlCl3·nEt2O
[0007] 3LiAlH4+AlCl3·nEt2O→4AlH3·nEt2O+3LiCl
[0008] AlH3·nEt2O→AlH3+nEt2O
[0009] The synthesis of AlH3 still faces numerous challenges. For instance, the intermediate ether compound obtained in the first step is highly unstable, easily decomposes and releases heat, posing a safety hazard. Filtration to remove LiCl precipitate is also required, inevitably leading to the loss of some of the precipitated product and incompletely dissolved raw materials. The resulting filter residue contains flammable components, requiring careful handling to prevent accidents. The prepared products are generally small in size, while the process for preparing larger products is complex. Furthermore, the lack of monitoring methods during the deetherification and crystallization process makes it impossible to determine the degree of reaction, easily resulting in the formation of non-α-crystalline AlH3 or incomplete deetherification.
[0010] Therefore, developing a large-size α-AlH3 synthesis method with high raw material utilization and a simple and efficient preparation process, and establishing a monitoring method for the deetherification and crystallization process, has important scientific application value. Summary of the Invention
[0011] This invention addresses the problem of complex reaction processes and potential safety hazards in the synthesis of α-AlH3 by providing a method for synthesizing large-sized α-aluminum trihydride. The method uses polysiloxane as a crystallizer, lowers the reaction temperature, and avoids the generation of unstable intermediate products and flammable precipitate residues, thereby obtaining larger-sized α-aluminum trihydride.
[0012] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0013] A method for synthesizing large-sized α-aluminum trihydride includes the following steps: mixing LiAlH4 solution and toluene solution of polysiloxane, heating to 60-80℃ and adding AlCl3 solution dropwise, reacting for 1-5 hours after the addition is completed, and washing and drying the precipitated product to obtain the large-sized α-aluminum trihydride.
[0014] In this invention, polysiloxane alone is used as a crystallizer to lower the crystallization temperature and increase the crystallization rate. High-purity α-aluminum trihydride is synthesized in one step. The preparation process is simple, the reaction conditions are mild, and there is no need to carry out the preparation under low temperature or high temperature and high pressure conditions. No unstable intermediate products or flammable precipitate residues are generated, and the reaction process is highly safe. The resulting product has a larger size and better storage stability, which can well meet the application requirements.
[0015] The solvent of the LiAlH4 solution includes one or more of benzene, toluene, xylene, n-hexane, n-heptane, tetrahydrofuran, dimethyl ether, diethyl ether, propyl ether, butyl ether, and ethylene glycol dimethyl ether; preferably, a mixed solvent prepared by diethyl ether, propyl ether, or butyl ether and toluene is more conducive to the formation of ether complexes during the synthesis process and more conducive to the deethering reaction during the deethering process.
[0016] The solvent for the AlCl3 solution includes one or more of benzene, toluene, xylene, n-hexane, n-heptane, tetrahydrofuran, dimethyl ether, diethyl ether, propyl ether, butyl ether, and ethylene glycol dimethyl ether. AlCl3 can dissolve in a variety of polar solvents and form complexes. In the dissolution process of AlCl3, different organic reagents can be selected as ligands for the complexes, preferably tetrahydrofuran, dimethyl ether, diethyl ether, propyl ether, butyl ether, and ethylene glycol dimethyl ether.
[0017] The polysiloxane is polymethylsiloxane or polydimethylsiloxane.
[0018] The polysiloxane has a viscosity of 10–100 mPa·s, a weight-average molecular weight of 1600–9000 g / mol, and is added at a mass of 5%–15% of AlCl3.
[0019] Preferably, the viscosity of the polysiloxane is 10-60 mPa·s. Studies have found that low-viscosity polymethylsiloxane or polydimethylsiloxane is more conducive to reducing the surface tension of the reaction solvent, thereby promoting the deetherification and crystallization of the ether compound in the solvent.
[0020] The reaction is carried out under the protection of an inert gas, such as nitrogen or argon. This process, including the preparation of the raw material solution and the reaction itself, involves repeatedly evacuating and then refilling with inert gas to ensure the reaction continues under this protection.
[0021] The AlCl3 solution was added at a rate of 10 mL / min to 30 mL / min. This rate allowed for a more complete reaction between aluminum chloride and lithium aluminum hydride. Adding the solution too quickly could result in incomplete reaction, causing the coordination number of the etherified compound to fail to meet the deetherification requirements, and also leading to waste of raw materials.
[0022] The molar ratio of LiAlH4 to AlCl3 is 3:1-4.5:1. According to the chemical reaction equation, 3 moles of LiAlH4 are required to react with 1 mole of AlCl3. In order for AlCl3 to react completely, LiAlH4 needs to be in excess. Excess LiAlH4 can also act as a catalyst for the deetherification reaction.
[0023] Washing of the precipitate includes washing with one or more of the following: ether and inorganic acid, water and ethanol.
[0024] Preferably, the precipitate is washed sequentially with diethyl ether, inorganic acid, water, ethanol, and diethyl ether to remove as much unreacted raw material and impurities as possible.
[0025] The filtrate from the initial ether washing of the precipitate was collected and used as a masterbatch. After adding LiAlH4 solution, it was mixed with a toluene solution of polysiloxane, followed by dropwise addition of AlCl3 solution for the next reaction to prepare large-sized α-aluminum trihydrogenate. Since there was an excess of LiAlH4 solution as a raw material during the reaction, it accumulated in the initial ether washing solution, which also included aluminum trihydrogenate ether compounds dissolved in the ether solvent. Therefore, this washing filtrate can be reused as a raw material, reducing reaction costs.
[0026] During the reaction process after the droplet addition, the refractive index of the distillate was measured. The reaction was considered complete when the refractive index of the distillate stabilized between 1.40 and 1.55. The inventors discovered that the deetherification and crystallization process can be monitored using refractive index measurement. When the refractive index of the distillate stabilizes at 1.40-1.55, the crystal transformation is essentially complete. This effectively overcomes the lack of reaction progress monitoring in existing α-AlH3 synthesis methods. This method can effectively and quickly identify the reaction completion time, improving time costs and product quality in actual production. During the deetherification and crystallization process, the reaction progress can be detected by measuring the refractive index of the distillate, preventing the formation of other unstable crystalline forms such as γ and β aluminum trihydride.
[0027] The synthesis method yields α-aluminum trihydride with a yield of over 90%, an α-crystal purity of over 90%, and a size of over 2 micrometers, preferably 2-30 μm.
[0028] Preferably, the purity of the α-aluminum trihydride α-crystal form obtained is above 95%.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The process of low-temperature preparation of ether compounds is omitted in the synthesis process of the present invention, which does not require an additional refrigeration device, thus reducing energy consumption. It also eliminates the need to prepare unstable ether compound solids, thereby reducing safety hazards in the production process.
[0031] (2) No mixed filter residue of LiCl, aluminum trihydride ether and undissolved LiAlH4 was generated during the synthesis process of this invention, which eliminated the need for post-processing and reduced product loss.
[0032] (3) The α-AlH3 crystals produced by this invention are larger in size than conventional crystals and have better storage stability.
[0033] (4) The present invention establishes a method for monitoring the deetherification and crystallization process, which can better control the reaction time required for the formation of α-AlH3. Attached Figure Description
[0034] Figure 1 The image shows the XRD pattern of α-AlH3 synthesized in Example 1.
[0035] Figure 2 The image shows the infrared spectrum of α-AlH3 synthesized in Example 1.
[0036] Figure 3 This is a scanning electron microscope image of the synthesized α-AlH3 in Example 1.
[0037] Figure 4 The image shows the XRD pattern of α-AlH3 synthesized in Example 2.
[0038] Figure 5 The image shows the infrared spectrum of α-AlH3 synthesized in Example 2.
[0039] Figure 6 This is a scanning electron microscope image of the synthesized α-AlH3 in Example 2.
[0040] Figure 7 The image shows the XRD pattern of α-AlH3 synthesized in Example 3.
[0041] Figure 8 The image shows the infrared spectrum of α-AlH3 synthesized in Example 3.
[0042] Figure 9 This is a scanning electron microscope image of the synthesized α-AlH3 in Example 3. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Modifications or equivalent substitutions made by those skilled in the art based on their understanding of the technical solutions of this invention, without departing from the spirit and scope of the invention, should be covered within the protection scope of this invention.
[0044] All raw materials used in the following specific implementation methods were purchased from the market.
[0045] Example 1
[0046] Step 1: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 82g of LiAlH4 in the single-necked flask, add 3.2L of a mixture of anhydrous diethyl ether and toluene (volume ratio 1:1), and stir continuously during the addition until the solid is completely dissolved.
[0047] Step 2: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 70g of anhydrous aluminum chloride in the single-necked flask and slowly add 900mL of a mixture of anhydrous diethyl ether and toluene (volume ratio 5:4). Stir continuously during the addition until the solid is completely dissolved.
[0048] Step 3: Dissolve 4g of crystallizing agent polymethylsiloxane (viscosity 10mPa·s, weight average molecular weight 1720g / mol) in 100mL toluene for later use.
[0049] Step 4: Vacuum the three-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the solution obtained in step (1) and the crystallizing agent prepared in step (3) to the reaction apparatus. Heat the reaction system to 80°C for distillation. When needle-like solids appear in the solution, slowly add anhydrous aluminum chloride solution at a rate of 10 mL / min, keeping the temperature fluctuation within ±1°C. Continue the reaction after the addition is complete. Stop the reaction when the refractive index of the distillate remains constant at 1.5. Allow the solution in the three-necked flask to cool to room temperature, let it stand to separate into layers, and filter it using a sintered glass funnel. Wash the filtered solid sequentially with 1600 mL of diethyl ether (collect and reuse), 100 mL of dilute hydrochloric acid, 500 mL of water, 100 mL of ethanol, and 100 mL of diethyl ether. Then, vacuum dry at 40°C for 24 h to obtain α-AlH3. After drying, 59.2 g of α-AlH3 solid product was obtained, with a yield of 93.96%.
[0050] Step 5: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the filtrate from the first ether washing in Step 4 as the mother liquor to the single-necked flask as the starting material for the new reaction. Add 75g of LiAlH4 and then 1600mL of toluene. Steps 2-4 can be repeated to prepare new α-AlH3.
[0051] The crystal form, chemical structure, and microstructure of the synthesized product were characterized using X-ray diffraction, infrared spectroscopy, and scanning electron microscopy, respectively. The test results are as follows: Figure 1-3 As shown. Figure 1 The results showed diffraction peaks at 2θ values of 27.84°, 38.58°, 40.72°, 46.1°, 49.96°, 57.26°, 63.26°, 66.26°, 68.14°, 72.48°, and 73.84°. The diffraction angles and peak intensities were consistent with the α-AlH3 diffraction data in the crystal diffraction library. No other impurity peaks were observed, indicating good crystallization of the product, with the crystals primarily being α-AlH3 and little or no other crystalline forms present. The purity of the α-AlH3 crystalline form was ≥98%.
[0052] Figure 2 The infrared spectral results show that the main vibrational peaks are located at 3452, 1853, 1724, 880, 732, and 670 cm⁻¹, respectively. -1 . Figure 3 The results show that the α-AlH3 particles are micron-sized cubic crystals with a random distribution of particle size between 5 and 30 μm.
[0053] Example 2
[0054] Step 1: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 82g of LiAlH4 in the single-necked flask, add 3.2L of a mixture of anhydrous propyl ether and toluene (volume ratio 1:1), and stir continuously during the addition until the solid is completely dissolved.
[0055] Step 2: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 70g of anhydrous aluminum chloride in the single-necked flask and slowly add 900mL of a mixed solvent of anhydrous propyl ether and toluene (volume ratio 5:4). Stir continuously during the addition until the solid is completely dissolved.
[0056] Step 3: Dissolve 4g of crystallizing agent polymethylsiloxane (viscosity 10mPa·s, weight average molecular weight 1720g / mol) in 100mL toluene for later use.
[0057] Step 4: Vacuum the three-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the solution obtained in step (1) and the crystallizing agent prepared in step (3) to the reaction apparatus. Heat the reaction system to 80°C and distill. When needle-like solids appear in the solution, slowly add anhydrous aluminum chloride solution at a rate of 10 mL / min, keeping the temperature fluctuation within ±1°C. Continue the reaction after the addition is complete. Stop the reaction when the refractive index of the distillate remains constant at 1.5. Allow the solution in the three-necked flask to cool to room temperature, let it stand to separate into layers, and filter it using a sintered glass funnel. Wash the filtered solid sequentially with 1600 mL of propyl ether (collect and reuse), 100 mL of dilute hydrochloric acid, 500 mL of water, 100 mL of ethanol, and 100 mL of diethyl ether. Then, vacuum dry at 40°C for 24 h to obtain α-AlH3. After drying, 58.5 g of α-AlH3 solid product was obtained, with a yield of 92.85%.
[0058] Step 5: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the filtrate from the first ether washing in Step 4 as the mother liquor to the single-necked flask as the starting material for the new reaction. Add 75g of LiAlH4 and then 1600mL of toluene. Steps 2-4 can be repeated to prepare new α-AlH3.
[0059] The crystal form, chemical structure, and microstructure of the synthesized product were characterized using X-ray diffraction, infrared spectroscopy, and scanning electron microscopy, respectively. The test results are as follows: Figure 4-6 As shown. Figure 4 The results showed diffraction peaks at 2θ values of 27.84°, 38.58°, 40.72°, 46.1°, 49.96°, 57.26°, 63.26°, 66.26°, 68.14°, 72.48°, and 73.84°. The diffraction angles and peak intensities were consistent with the α-AlH3 diffraction data in the crystal diffraction library. No other impurity peaks were observed, indicating good crystallization of the product, with the crystals primarily being α-AlH3 and little or no other crystalline forms present. The purity of the α-AlH3 crystalline form was ≥99%. Figure 5 The results show that the main vibrational peaks are located at 3449, 1846, 1722, 886, 759, and 676 cm⁻¹, respectively. -1 . Figure 6 The results showed that the α-AlH3 particles were randomly distributed between 5 and 30 μm in size, and the crystals were spherical.
[0060] Example 3
[0061] Step 1: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 82g of LiAlH4 in the single-necked flask and add 3.2L of a mixed solvent of anhydrous diethyl ether and toluene (volume ratio 1:1). Stir continuously during the addition until the solid is completely dissolved.
[0062] Step 2: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 70g of anhydrous aluminum chloride in the single-necked flask and slowly add 900mL of a mixture of anhydrous diethyl ether and toluene (volume ratio 5:4). Stir continuously during the addition until the solid is completely dissolved.
[0063] Step 3: Dissolve 4g of crystallizing agent polymethylsiloxane (viscosity 30mPa·s, weight average molecular weight 3580g / mol) in 150mL toluene for later use.
[0064] Step 4: Vacuum the three-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the solution obtained in step (1) and the crystallizing agent prepared in step (3) to the reaction apparatus. Heat the reaction system to 80°C for distillation. When needle-like solids appear in the solution, slowly add anhydrous aluminum chloride solution at a rate of 10 mL / min, keeping the temperature fluctuation within ±1°C. Continue the reaction after the addition is complete. Stop the reaction when the refractive index of the distillate remains constant at 1.5. Allow the solution in the three-necked flask to cool to room temperature, let it stand to separate into layers, and filter it using a sintered glass funnel. Wash the filtered solid sequentially with 1600 mL of diethyl ether (collect and reuse), 100 mL of dilute hydrochloric acid, 500 mL of water, 100 mL of ethanol, and 100 mL of diethyl ether. Then, vacuum dry at 40°C for 24 h to obtain α-AlH3. After drying, 56.9 g of α-AlH3 solid product was obtained, with a yield of 90.31%.
[0065] Step 5: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the filtrate from the first ether washing in Step 4 as the mother liquor to the single-necked flask as the starting material for the new reaction. Add 75g of LiAlH4 and then 1600mL of toluene. Steps 2-4 can be repeated to prepare new α-AlH3.
[0066] The crystal form, chemical structure, and microstructure of the synthesized product were characterized using X-ray diffraction, infrared spectroscopy, and scanning electron microscopy, respectively. The test results are as follows: Figure 7-9 As shown. Figure 7 The results showed diffraction peaks at 2θ values of 27.84°, 38.58°, 40.72°, 46.1°, 49.96°, 57.26°, 63.26°, 66.26°, 68.14°, 72.48°, and 73.84°. The diffraction angles and peak intensities were consistent with the α-AlH3 diffraction data in the crystal diffraction library. No other impurity peaks were observed, indicating good crystallization of the product, with the crystals primarily being α-AlH3 and little or no other crystalline forms present. The purity of the α-AlH3 crystalline form was ≥97%. Figure 8 The results show that the main vibrational peaks are located at 3459, 1854, 1717, 888, 749, and 674 cm⁻¹, respectively. -1 . Figure 9 The results show that the α-AlH3 particles are spherical crystals with a size of about 5 μm.
[0067] Example 4
[0068] Step 1: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 82g of LiAlH4 in a single-necked flask and add 3.2L of a mixed solvent of anhydrous diethyl ether, toluene, and n-heptane. The volume ratio of anhydrous diethyl ether, toluene, and n-heptane is 1:1:0.3. Stir continuously during the addition process until the solid is completely dissolved. Set aside for later use.
[0069] Step 2: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 70g of anhydrous aluminum chloride in the single-necked flask and slowly add 900mL of a mixture of anhydrous diethyl ether and toluene (volume ratio 5:4). Stir continuously during the addition until the solid is completely dissolved.
[0070] Step 3: Dissolve 3g of crystallizing agent polymethylsiloxane (viscosity 50mPa·s, weight-average molecular weight 6110g / mol) and 3g of polydimethylsiloxane (viscosity 30mPa·s, weight-average molecular weight 3580g / mol) in 150mL of toluene for later use.
[0071] Step 4: Vacuum the three-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the solution obtained in step (1) and the crystallizing agent prepared in step (3) to the reaction apparatus. Heat the reaction system to 75°C and distill. When needle-like solids appear in the solution, slowly add anhydrous aluminum chloride solution at a dropping rate of 20 mL / min, keeping the temperature fluctuation within ±1°C. Continue the reaction after the addition is complete. Stop the reaction when the refractive index of the distillate remains constant at 1.48. Allow the solution in the three-necked flask to cool to room temperature, let it stand to separate into layers, and filter it using a sintered glass funnel. Wash the filtered solid sequentially with 1600 mL of diethyl ether (collect and reuse), 100 mL of dilute hydrochloric acid, 500 mL of water, 100 mL of ethanol, and 100 mL of diethyl ether. Then, vacuum dry at 40°C for 24 h to obtain α-AlH3. After drying, 57.1 g of α-AlH3 solid product was obtained, with a yield of 90.63%.
[0072] Step 5: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the filtrate from the first ether washing in Step 4 as the mother liquor to the single-necked flask as the starting material for the new reaction. Add 75g of LiAlH4 and then 1600mL of toluene. Steps 2-4 can be repeated to prepare new α-AlH3.
[0073] XRD and scanning electron microscopy results show that the prepared AlH3 is α-crystalline, with a purity ≥98%, and is a micron-sized blocky crystal with a size of 5-10 μm.
[0074] Example 5
[0075] Step 1: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 82g of LiAlH4 in a single-necked flask and add 3.2L of a mixed solvent of anhydrous propyl ether and toluene. The volume ratio of anhydrous propyl ether, toluene, and n-hexane is 1:1:0.5. Stir continuously during the addition until the solid is completely dissolved. Set aside for later use.
[0076] Step 2: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 70g of anhydrous aluminum chloride in the single-necked flask and slowly add 900mL of a mixture of anhydrous propyl ether and toluene (volume ratio of anhydrous ethyl ether to toluene: 1:1). Stir continuously during the addition until the solid is completely dissolved.
[0077] Step 3: Dissolve 2g of crystallizing agent polymethylsiloxane (viscosity 50mPa·s, weight-average molecular weight 6110g / mol) and 4g of polydimethylsiloxane (viscosity 80mPa·s, weight-average molecular weight 8340g / mol) in 150mL of toluene for later use.
[0078] Step 4: Vacuum the three-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the solution obtained in step (1) and the crystallizing agent prepared in step (3) to the reaction apparatus. Heat the reaction system to 65°C for distillation. When needle-like solids appear in the solution, slowly add anhydrous aluminum chloride solution at a dropping rate of 20 mL / min, keeping the temperature fluctuation within ±1°C. Continue the reaction after the addition is complete. Stop the reaction when the refractive index of the distillate remains constant at 1.52. Allow the solution in the three-necked flask to cool to room temperature, let it stand to separate into layers, and filter it using a sintered glass funnel. Wash the filtered solid sequentially with 1600 mL of propyl ether (collect and reuse), 100 mL of dilute hydrochloric acid, 500 mL of water, 100 mL of ethanol, and 100 mL of diethyl ether. Then, vacuum dry at 40°C for 24 h to obtain α-AlH3. After drying, 59.0 g of α-AlH3 solid product was obtained, with a yield of 93.65%.
[0079] Step 5: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the filtrate from the first ether washing in Step 4 as the mother liquor to the single-necked flask as the starting material for the new reaction. Add 75g of LiAlH4 and then 1600mL of toluene. Steps 2-4 can be repeated to prepare new α-AlH3.
[0080] XRD and scanning electron microscopy results show that the prepared AlH3 is α-crystalline with a purity ≥98%, and is in the form of micron-sized blocky and spherical crystals with a size of about 10 μm.
[0081] Example 6
[0082] Step 1: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 82g of LiAlH4 in a single-necked flask and add 3.2L of a mixed solvent of anhydrous diethyl ether and toluene. The volume ratio of anhydrous diethyl ether, xylene, and n-heptane is 1:1:0.5. Stir continuously during the addition until the solid is completely dissolved. Set aside for later use.
[0083] Step 2: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. At room temperature, place 70g of anhydrous aluminum chloride in the single-necked flask and slowly add 900mL of a mixed solvent of anhydrous diethyl ether and xylene (volume ratio 1:1). Stir continuously during the addition until the solid is completely dissolved.
[0084] Step 3: Dissolve 2g of crystallizing agent polymethylsiloxane (viscosity 50mPa·s, weight average molecular weight 6110g / mol) and 4g of polydimethylsiloxane (viscosity 80mPa·s, weight average molecular weight 8340g / mol) in 150mL of xylene for later use.
[0085] Step 4: Vacuum the three-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the solution obtained in step (1) and the crystallizing agent prepared in step (3) to the reaction apparatus. Heat the reaction system to 80°C and distill. When needle-like solids appear in the solution, slowly add anhydrous aluminum chloride solution at a rate of 30 mL / min, keeping the temperature fluctuation within ±1°C. Continue the reaction after the addition is complete. Stop the reaction when the refractive index of the distillate remains constant at 1.52. Allow the solution in the three-necked flask to cool to room temperature, let it stand to separate into layers, and filter it using a sintered glass funnel. Wash the filtered solid sequentially with 1600 mL of diethyl ether (collect and reuse), 100 mL of dilute hydrochloric acid, 500 mL of water, 100 mL of ethanol, and 100 mL of diethyl ether. Then, vacuum dry at 40°C for 24 h to obtain α-AlH3. After drying, 57.6 g of α-AlH3 solid product was obtained, with a yield of 91.42%.
[0086] Step 5: Evacuate the single-necked flask, then purge it with nitrogen to remove air. Repeat this process three times. Add the filtrate from the first ether washing in Step 4 as the mother liquor to the single-necked flask as the starting material for the new reaction. Add 75g of LiAlH4 and then 1600mL of toluene. Steps 2-4 can be repeated to prepare new α-AlH3.
[0087] XRD and scanning electron microscopy results show that the prepared AlH3 is α-crystal with a purity ≥97%, and is a micron-sized irregular spherical crystal with a size of about 5 μm.
[0088] In terms of size, the aluminum hydride prepared in Example 1 has the largest size, indicating that it has better storage performance, is not easily decomposed, and has the highest yield.
[0089] Comparative Example 1
[0090] Compared to Example 1, the difference lies in the polymethylsiloxane used in step 3 (viscosity 200 mPa·s, weight-average molecular weight 1.5 × 10⁻⁶). 4 The experimental conditions were kept constant (g / mol). The AlH3 prepared in this experiment was in the α-crystal form, with a yield of 85% and a purity of ≥97%. It was an irregular spherical crystal with a size of approximately 500 nm.
[0091] Comparative Example 2
[0092] Compared to Example 1, the difference lies in the dropping rate of the anhydrous aluminum chloride solution in step 4, which is 100 mL / min; all other experimental conditions remain the same. During the dropping process, a violent reaction occurs in the reactor, raising the solvent temperature by approximately 15°C, which is detrimental to the stable progress of the reaction and increases the reaction risk. The AlH3 prepared in this experiment is a mixture of α- and α'-crystal forms, with a yield of 60% and a purity ≥85%. It exists as irregular spherical crystals with a size of approximately 200–500 nm.
[0093] Comparative Example 3
[0094] Compared to Example 1, the difference lies in step 4: the three-necked flask is evacuated, and then nitrogen gas is introduced into the flask to remove the air inside. This operation is repeated three times. Anhydrous aluminum chloride solution is added to the reaction apparatus. The solution obtained in step (1) and the crystallizing agent prepared in step (3) are slowly added dropwise to the reaction apparatus, maintaining a dropping rate of 10 mL / min. After the addition is complete, the temperature of the reaction system is raised to 80°C for the reaction. All other experimental conditions remain the same. XRD analysis shows that α-crystalline AlH3 was not successfully prepared in this experiment. The X-ray diffraction peaks at low angles show a "bun-like" peak similar to that of ether compounds, indicating that the deetherification reaction failed. This shows that the order of addition has a significant impact on the reaction.
Claims
1. A method for synthesizing large-sized α-aluminum trihydride, characterized in that, The steps include: mixing LiAlH4 solution and toluene solution of polysiloxane, heating to 60-80℃ and adding AlCl3 solution dropwise, reacting for 1-5 hours after the addition is complete, washing and drying the precipitate to obtain the large-sized α-aluminum trihydride; The polysiloxane has a viscosity of 10–100 mPa·s, a weight-average molecular weight of 1600–9000 g / mol, and is added at a mass of 5%–15% of AlCl3; the molar ratio of LiAlH4 to AlCl3 is 3:1–4.5:
1. The AlCl3 solution was added at a rate of 10 mL / min to 30 mL / min. The solvent of the LiAlH4 solution includes one or more of tetrahydrofuran, dimethyl ether, diethyl ether, propyl ether, butyl ether, and ethylene glycol dimethyl ether. The solvent of the AlCl3 solution includes one or more of tetrahydrofuran, dimethyl ether, diethyl ether, propyl ether, butyl ether, and ethylene glycol dimethyl ether. The polysiloxane is polymethylsiloxane or polydimethylsiloxane.
2. The method for synthesizing large-size α-aluminum trihydride according to claim 1, characterized in that, The reaction is carried out under the protection of an inert gas.
3. The method for synthesizing large-size α-aluminum trihydride according to claim 1, characterized in that, Washing of the precipitate product includes washing with one or more solvents selected from diethyl ether and inorganic acid, water, and ethanol.
4. The method for synthesizing large-size α-aluminum trihydride according to claim 1, characterized in that, The precipitate was first washed with ether and the filtrate was collected as a masterbatch. After adding LiAlH4 solution, it was mixed with toluene solution of polysiloxane and AlCl3 solution was added dropwise to carry out the next reaction to prepare large-sized α-aluminum trihydrogenate.
5. The method for synthesizing large-size α-aluminum trihydride according to claim 1, characterized in that, During the reaction process after the addition of the first drop, the refractive index of the distillate was measured. When the refractive index of the distillate stabilized at 1.40-1.55, the reaction was considered to be complete.
6. The method for synthesizing large-size α-aluminum trihydride according to claim 1, characterized in that, The synthesis method yields α-aluminum trihydride with a yield of over 90%, an α-crystal purity of over 90%, and an average size of over 2 μm.
Citation Information
Patent Citations
Improved process for preparing alpha-aluminum hydride
CN106957046A
Alpha-aluminum hydride preparation method
CN107098313A
Alpha-aluminum trihydride synthesis technology
CN109970030A
Chemical catalytic preparation method of high-purity alpha-aluminum hydride
CN114988366A
Aluminum hydride and preparation method thereof
CN115974002A
